A pre-operative prognostic score for the selection of patients for salvage surgery after recurrent head and neck squamous cell carcinomas - Valentina Lupato; Jerry Polesel; Fabio Biagio La Torre; Giuseppe Fanetti; Elisabetta Fratta; Carlo Gobitti; Gustavo Baldassarre; Emanuela Vaccher; Giovanni Franchin; Vittorio Giacomarra (Scientific Reports, 2021)
Abstract Salvage surgery in recurrent head and neck squamous cell carcinoma has a poor outcome, both in terms of survival and quality of life. Therefore, the identification of pre-operative prognostic factors to improve the selection of patients who could benefit the most from salvage surgery is clinically relevant. The present study is a single-center retrospective analysis of 164 patients treated with salvage surgery after recurrence of head and neck cancer. Progression free survival and overall survival were calculated through Kaplan–Meier method. Hazard risk (HR) and corresponding confidence intervals (CI) were estimated through Cox proportional hazard model, adjusting for potential confounders. Significant predictors were combined into a prognostic score, attributing one point to each factor. Progression-free survival and overall survival were respectively 50.3% and 56.5% at 2 years, and 36.6% and 44.2% at 5 years. Four pre-operative factors were independently associated with poor prognosis: age > 70 years (HR = 2.18; 95% CI 1.27–3.73), initial stage IV (HR = 2.37; 95% CI 1.18–4.76), disease free interval < 12 months (HR = 1.72; 95% CI 1.01–2.94), and loco-regional recurrence (HR = 2.22; 95% CI 1.22–4.04). No post operative factor was associated with oncologic outcomes. Patients with 3–4 unfavorable factors showed a 5-year overall survival of 0.0% compared to 65.7% in those with 0–1 unfavorable factors (HR = 5.61; 95% CI 2.89–10.92). Despite the low number of patients, 3–4 unfavorable factors were associated to worse prognosis in all sub-sites. In conclusion, age > 70 years, initial stage IV, disease-free interval < 12 months, and loco-regional recurrence are strong independent pre-operative predictors of poor outcome in patients undergoing salvage surgery. Patients with two or more of these factors should be informed about the low success rate after salvage surgery and alternative treatments should be considered.